Sarcoidosis and autoimmunity. Issue 5 (September 2021) - Song, Minhyuk; Manansala, Michael; Parmar, Prashant J.; Ascoli, Christian; Rubinstein, Israel; Sweiss, Nadera J.
Abstract : Purpose of review: Sarcoidosis is a poorly understood multisystem granulomatous disease that frequently involves the lungs but can affect any organ system. In this review, we summarize recent developments in the understanding of the immune dysregulation seen in sarcoidosis and propose a new expanded definition of human autoimmunity in sarcoidosis, and the implications it would have on treating sarcoidosis with targeted immunotherapy regimens in the future. Recent findings: Sarcoidosis has been linked to infectious organisms like Mycobacterium and Cutibacterium, and certain manifestations of sarcoidosis have been linked to specific HLA alleles, but the overall pathogenesis remains uncertain. Sarcoidosis patients have similar patterns of cellular immune dysregulation seen in other autoimmune diseases like rheumatoid arthritis, and recent large-scale population studies show that sarcoidosis frequently presents with other autoimmune diseases. Summary: Advancements in the understanding of sarcoidosis support its consideration as an autoimmune disease. Sarcoidosis patients carry a higher risk of comorbid autoimmune conditions which offers an excellent opportunity to further understand autoimmunity and explore biologic therapies in sarcoidosis treatment, and furthermore will better targeted immunotherapy regimens for sarcoidosis patients in the future.